THE RELATIONSHIP BETWEEN BODY WEIGHT AND BODY CONDITION SCORE SOME INDIGENOUS SHEEP BREEDS IN TURKEY - T. Sezenler; M. Özder; M. Yıldırır; A. Ceyhan; M. A.Yüksel (Journal of Animal and Plant Sciences, 2011)
This study was carried out on Kivircik, Sakiz and Gokceada sheep bred at Marmara Livestock Research Institute. A total of 156 heads sheep from different age groups were used in the study. The relationships between Body Condition Scores (BCS) and Body Weights (BW) have been investigated in three different physiological periods such as breeding, lambing and weaning period of indigenous sheep breeds in Turkey. As a result of the analyses conducted, the relationship between body condition score and body weight were found to be BW = 28.716+6.962* BCS; BW = 39.977+6.771* BCS; BW = 33.444+7.074* BCS for the breeding, lambing and weaning periods respectively. Similarly, correlations (r) between them were found to be 0.817, 0.731, 0.746 respectively (P<0.01). The regression coefficients of BCS on BW were 6.962 kg, 6.771 kg, 7.074 kg at breeding, lambing, weaning respectively and also significant (P<0.01). The findings demonstrate that body condition score is a good indicator of changes in body weights in Kivircik, Sakiz and Gokceada indigenous sheep breeds and will assist sheep breeders with regard to the feeding program to be applied particularly before the breeding season.
Keywords: Body condition score; body weight; Kivircik; Sakiz; Gokceada.